Carbamate pesticides exposure and delayed physical development at the age of seven: Evidence from the SMBCS study. (February 2022) - Zhang, Jiming; Guo, Jianqiu; Wu, Chunhua; Qi, Xiaojuan; Jiang, Shuai; Lv, Shenliang; Lu, Dasheng; Liang, Weijiu; Chang, Xiuli; Zhang, Yubin; Cao, Yang; Zhou, Zhijun
Graphical abstract: Highlights: Carbofuranphenol concentrations with high detection rates of prenatal, 3-year-old, 7-year-old periods were applied to accurately access long-term carbamate exposure and its health effects on physical development. Anthropometric indices of children aged 7 years old were reversely associated with prenatal and postnatal urinary carbofuranphenol concentrations. The trends of both significant gender-interaction and gender differential were observed in generalized linear models and generalized estimated equations. Adverse effect of carbamates on physical development may have a postnatal sensitive window showed by time-interaction analysis. Abstract: Background: Carbamate pesticides are widely used in agriculture and cause widespread human exposure. The health effect of carbamates on physical development remains unclear. The current study aimed to explore the carbamate's health effect on physical development. Methods: Prenatal, 3-year-old, 7-year-old urinary carbofuranphenol concentration was measured by gas chromatography tandem mass spectrometry and adjusted by creatinine. Anthropometric indices were measured by standard method and z-score standardized. Generalized linear models (GLM) were using to assess associations between exposure measurements and anthropometric indices. The generalized estimate equation (GEE) was applied to analyze the association between multiperiod exposure and anthropometric indices, and time-interaction terms were used to exam health effect consistency of exposure in each period. Gender-stratified analysis were conducted according to results of gender-interaction terms to identify gender-specific effects. Results: The gender-interaction term of prenatal exposure with height z-score was significant (β = -0.057; 95% CI: −0.113, −0.001; p = 0.045). The 3-year-old carbofuranphenol level showed negative associations with weight z-score (β = -0.019; 95% CI: −0.038, −0.000; p = 0.040), height z-score (β = -0.015; 95% CI: −0.028, −0.001; p = 0.026), chest circumference (β = -0.086; 95% CI: −0.171, −0.001; p = 0.046), and waist circumference (β = -0.128; 95% CI: −0.230, −0.026; p = 0.014). No statistically significant trend was found for prenatal and 7-year-old carbofuranphenol levels. In GEEs, carbofuranphenol level was negatively associated with weight z-score (β = -0.103; 95% CI: −0.195, −0.011; p = 0.027), height z-score (β = -0.087; 95% CI: −0.152, −0.022; p = 0.008), and chest circumference (β = -0.472; 95% CI: −0.918, −0.026; p = 0.037). Boy's height z-score was inversely associated with carbamate exposure (β = -0.140; 95% CI: −0.227, −0.053; p = 0.001). Conclusions: Prenatal and postnatal carbamate exposure may affect physical developmental process.